Antibacterial Activity Test of Lissoclinum patella Extract Obtained from the Coastal Waters of Parentek Village, East Lembean District, Minahasa Regency - Kiwol, Hilda; Wewengkang, Defny; Rumondor, Erladys (PHARMACON, 2024)
Ascidians are a class of marine tunicates that are included in marine invertebrate organisms. Tunicates (Ascidian) are animals included in the subphylum Urochordata, which have a small bag-like body shape and generally live in marine waters. The body of this animal is covered by a coat (tunic) formed from protein and polysaccharide compounds. This study aims to determine the antibacterial activity of ethanol extract of ascidian Lissoclinum patella against the growth of Staphylococcus aureus and Escherichia coli bacteria. Extraction uses maceration method to extract active compounds from ascidian Lissoclinum patella. The results of the extract were tested whether there was antibacterial activity against Staphylococcus aureus and Escherichia coli bacteria, the test used the Kirby-Bauer agar diffusion method. The results of the test showed antibacterial activity with a marked inhibition zone around the disc paper of the extract test solution on Staphylococcus aureus bacteria with a medium inhibition zone diameter of 7.6 mm and Escherichia coli bacteria with a medium inhibition zone diameter of 6.3 mm.